Maxwell hybrid nanofluid on mixed convective radiative flow over a stretching plate with nanoparticle shapes effect / Ain Sofiah Johan Arifin, Nur Iz’zah Syafikah Mohd Nazri and Siti Sarah Azahar - Johan Arifin, Ain Sofiah; Mohd Nazri, Nur Iz’zah Syafikah; Azahar, Siti Sarah (2024)
This study explored the Maxwell hybrid nanofluid on mixed convective radiative flow over the stretching plate with nanoparticle shapes effect. This study aims to increase the efficiency of heat transfer fluids by using hybrid nanofluid. The objectives include extending a mathematical model of Maxwell hybrid nanofluid flow on a stretching plate heated by convective boundary condition and determining the impact of governing parameters on the profiles of velocity, temperature, skin friction, and the local Nusselt number. The study uses sodium alginate (NaALG) with copper (cu) and aluminium oxide (AI2 O3) nanoparticles, and considers various shapes, including spherical, brick-shaped, cylindrical, and platelet-shaped nanoparticle. The governing nonlinear partial differential equations to nonlinear ordinary differential equations are converted by using similarity transformation and ordinary differential equations are solved using the bvp4c solver. MATLAB software is used for implementation. Parameters that use in this research are aligned angle of magnetic field, interaction of magnetic field, Maxwell parameter, mixed convection, stretching/shrinking parameter, radiation parameter, convection boundary condition, and volume fraction of nanoparticles. The result show that the velocity profiles increase while temperature profiles decrease for the increasing parameters aligned angle of magnetic field, interaction of magnetic field, Maxwell parameter, mixed convective, stretching/shrinking parameter and volume fraction of nanoparticle. When the radiation parameter and Biot number associated with the convective boundary condition increase, then the velocity and temperature profiles will also increase. The values of skin fiction and Nusselt number increase due to the parameters aligned angle of magnetic field, interaction of magnetic field, maxwell parameter, radiation parameter and convection boundary condition increase except for the parameters stretching/ shrinking parameter and volume fraction of nanoparticle. Therefore, the skin friction and Nusselt number have different values for all the nanoparticles shapes. Spherical nanoparticles demonstrate the highest velocity and temperature profiles, followed by bricks, cylindrical, and platelet shapes.